THE INFLUENCE OF BRAND IMAGE AND PRODUCT QUALITY ON PURCHASE INTENTION IN VIVO SMARTPHONES OF TOBA REGENCY - Eva Margareth Sarah; Niscaya Hia; Monalisa Panjaitan (International Journal Management and Economic, 2024)
This study was conducted with the aim of knowing whether there is an effect of brand image and product quality on purchase intention in vivo smartphones on employees of the Office of Cooperatives, Small and Medium Enterprises, Trade and Industry of Toba Regency. The research method used is descriptive quantitative research method, namely by looking to distribute questionnaires to find out information about existing symptoms in Vivo smartphone user consumers and using multiple linear regression analysis methods. The data used in this study are primary data and secondary data. The sample in this study amounted to 85 people with a sampling technique that is taking the entire population. The data is processed statistically using the SPSS 23 for windows program tool. The results of this study indicate that Brand Image has a positive and significant effect on purchase intention with a tcount value greater than the ttable (2.469> 1.66342) and Product Quality has a positive and significant effect on purchase intention with a tcount value greater than the ttable (3.243> 1.66342). So brand image and product quality affect the Purchase Intention of vivo smartphone products on employees of the Toba Regency Cooperative, Small and Medium Enterprises, Trade and Industry Service Office with a value of fcount greater than ftable (26.197> 3.11).